A monolithically integrated opto-electronic clock converter in photonic SiGe-BiCMOS technology - Krueger, B.; Makon, R. E.; Landolt, O.; Krune, E.; Knoll, D.; Lischke, S.; Schulze, J. (Proceedings of the IEEE Bipolar/BiCMOS Circuits and Technology Meeting, 2015)
A novel monolithic opto-electronic clock converter integrated in a photonic SiGe-BiCMOS technology is presented, which turns an ultrashort optical pulse train generated by a hybrid mode-locked laser into a low-jitter electrical square wave with sharp transitions. The integrated circuit includes optical waveguides as well as grating couplers, a high-bandwidth (> 30 GHz) Ge-photodiode, a frequency divider-by-two implemented by SiGe bipolar transistors, photodiode characterization circuits and an optical monitoring path. The integrated circuit has been successfully tested at laser pulse repetition rates of up to 10 GHz. At this pulse repetition rate, the generated 5 GHz electrical square wave signal features a wideband phase noise floor <-160 dBc/Hz and an jitter tj < 1 fs while integrating the phase noise at offset frequencies between 2 kHz and 30 MHz.
CRIS-Team Scopus Importer:2021-06-29